23.2k views
2 votes
2x + 2y + z = 2
-x + 3y + z = -2
3x + 2z = 7

1 Answer

1 vote

Answer:


x=1,\:\\z=2,\:\\y=-1

Explanation:


\begin{bmatrix}2x+2y+z=2\\ -x+3y+z=-2\\ 3x+2z=7\end{bmatrix}\\\\\mathrm{Multiply\:}-x+3y+z=-2\mathrm{\:by\:}2\:\mathrm{:}\:\quad \:-2x+6y+2z=-4\\\\\begin{bmatrix}2x+2y+z=2\\ -2x+6y+2z=-4\\ 3x+2z=7\end{bmatrix}\\\\-2x+6y+2z=-4\\+\\\underline{2x+2y+z=2}\\8y+3z=-2\\\\\begin{bmatrix}2x+2y+z=2\\ 8y+3z=-2\\ 3x+2z=7\end{bmatrix}\\\\\mathrm{Multiply\:}2x+2y+z=2\mathrm{\:by\:}3\:\mathrm{:}\:\\\quad \:6x+6y+3z=6\\\\\mathrm{Multiply\:}3x+2z=7\mathrm{\:by\:}2\:\mathrm{:}\:\quad \:6x+4z=14\\\\


\begin{bmatrix}6x+6y+3z=6\\ 8y+3z=-2\\ 6x+4z=14\end{bmatrix}\\\\6x+4z=14\\-\\\underline{6x+6y+3z=6}\\-6y+z=8\\\\\begin{bmatrix}6x+6y+3z=6\\ 8y+3z=-2\\ -6y+z=8\end{bmatrix}\\\\\mathrm{Multiply\:}8y+3z=-2\mathrm{\:by\:}3\:\mathrm{:}\:\\\quad \:24y+9z=-6\\\\\mathrm{Multiply\:}-6y+z=8\mathrm{\:by\:}4\:\mathrm{:}\:\\\quad \:4z-24y=32\\\\\begin{bmatrix}6x+6y+3z=6\\ 24y+9z=-6\\ -24y+4z=32\end{bmatrix}\\\\-24y+4z=32\\+\\\underline{24y+9z=-6}\\13z=26


\begin{bmatrix}6x+6y+3z=6\\ 24y+9z=-6\\ 13z=26\end{bmatrix}\\\\Solve\:13z=26\:for\:z\: : , z= 2\\\\\mathrm{For\:}24y+9z=-6\mathrm{\:plug\:in\:}z=2\\\\Solve\:24y+9*\:2=-6\:for\:y\:,y=-1\\\\\mathrm{For\:}6x+6y+3z=6\mathrm{\:plug\:in\:}z=2,\:y=-1\\\\Solve\:6x+6\left(-1\right)+3*\:2=6\:for\:x\:,x=1\\\\x=1,\:z=2,\:y=-1

User Thandi
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.